2022
DOI: 10.1002/lpor.202200698
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Property Prediction with Photonic Chip‐Based Machine Learning

Abstract: Machine learning methods have revolutionized the discovery process of new molecules and materials. However, the intensive training process of neural networks for molecules with ever‐increasing complexity has resulted in exponential growth in computation cost, leading to long simulation time and high energy consumption. Photonic chip technology offers an alternative platform for implementing neural networks with faster data processing and lower energy usage compared to digital computers. Photonics technology is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Meanwhile, Dwivedi et al reported the use of machine learning models on different datasets vis-a-vis fiber-optic plasmonic sensor devices. The modeled data is found to be highly consistent with the data in terms of trend matching, and the values of other parameters such as R^2 and mean absolute error [29]. On the other hand, in our previous studies, we used deep neural network (DNN) techniques to predict the beam properties of light coupled from grating structures to free space.…”
Section: Introductionmentioning
confidence: 54%
“…Meanwhile, Dwivedi et al reported the use of machine learning models on different datasets vis-a-vis fiber-optic plasmonic sensor devices. The modeled data is found to be highly consistent with the data in terms of trend matching, and the values of other parameters such as R^2 and mean absolute error [29]. On the other hand, in our previous studies, we used deep neural network (DNN) techniques to predict the beam properties of light coupled from grating structures to free space.…”
Section: Introductionmentioning
confidence: 54%
“…Although ANNs inherently introduce systematic errors into optimization processes, these errors, typically within a few percent, do not negate the advantages of DL-based methods characterizing by strong fitting capabilities and high evaluation speeds. Driven by currently emerging technologies such as photonic chips [159][160][161][162] and quantum computing [163][164][165][166], these advantages can be even further expanded. Overall, as DL theories advance and computer performance improves, it is reasonable to anticipate that DLbased inverse design methods will play a vital role in realizing disruptive EM metamaterial designs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…On-chip (online) PNN training can improve prediction accuracy, and it is classified into two main categories: gradient-free and numerical-gradientbased. Gradient-free methods employ non-gradient search algorithms, such as genetic algorithms, [13,14] biologically inspired method [15] and particle swarm optimization [16] to obtain optimal solutions. While these approaches yield high accuracy in simple classification tasks, their computation complexity increases significantly with the number of trainable parameters, restricting their scalability for complicated machine-learning tasks.…”
Section: Introductionmentioning
confidence: 99%